Student Attendance at Library Workshops: What the Data Tells Us - Witherspoon, Richelle (Université d'Ottawa | University of Ottawa, 2018)
What makes students come to workshops, and what can we do to increase their numbers? This presentation describes a study that compiled data from workshops across Canada and the US in order to determine the factors that influence student attendance at library and support workshops. Best practices will be discussed.